Ensuring the Women's Political Agenda: A Study of Women Members of Parliament in Nine Regencies/Cities in Eastern Indonesia - Abdul Madjid Sallatu; NFN Rahmadani; NFN Agussalim; Abby Gina Boangmanalu (Yayasan Jurnal Perempuan, 2019)
Representation of women in the legislature is important. The presence of women members of parliament (MPs) does not only balance the number of parliamentarians (gender balance), but also encourages women’s issues to be a priority, so that various gender sensitive policies are born. This study focuses on women legislator in nine regencies/cities of Eastern Indonesia, namely: Maros Regency, Bone Regency, Tana Toraja Regency, Parepare City, Mataram City, East Lombok Regency, Kendari City, Belu Regency and Ambon City. This study looks at women legislator’s portraits in nine research areas, obstacles in implementing main tasks and functions as women legislator and relations with various related groups. This study applies a phased mixed method design that focuses on qualitative studies. Data collection is done through document review, surveys, and in-depth interviews. This research found that in order to guarantee the struggle for women’s political agenda, capacity building was needed for Parliamentary Members of Women in Eastern Indonesia.